Regulation of mammalian ribosomal gene transcription by RNA polymerase I - Grummt, Ingrid (Progress in nucleic acid research and molecular biology, 1998)
All cells, from prokaryotes to vertebrates, synthesize vast amounts of ribosomal RNA to produce the several million new ribosomes per generation that are required to maintain the protein synthetic capacity of the daughter cells. Ribosomal gene (rDNA) transcription is governed by RNA polymerase I (Pol I) assisted by a dedicated set of transcription factors that mediate the specificity of transcription and are the targets of the pleiotrophic pathways the cell uses to adapt rRNA synthesis to cell growth. In the past few years we have begun to understand the specific functions of individual factors involved in rDNA transcription and to elucidate on a molecular level how transcriptional regulation is achieved. This article reviews our present knowledge of the molecular mechanism of rDNA transcriptional regulation.